De-facing the other : reason, ethics, & politics after difference - Minister, Stephen (Marquette studies in philosophy ;, 2012)
In an often overlooked passage, Emmanuel Levinas states that we must de-face humans, sternly reducing each ones uniqueness to his individuality in the unity of the genus, and let universality rule. How can Levinas, the great thinker of infinite alterity and the face of the other, make such a provocative claim? This book argues that understanding this claim is the key to unlocking the possibility of positive, constructive ethical and political thought and practice in the wake of the discourse on difference. In contrast to the excessive negativity of some postmodern thought, this book argues for a positive postmodernism that reconceptualizes reason and identity on the basis of ethical responsibility. This in turn makes possible the rational construction of identities necessary for ethical and political thought and practice. In making a case for this possibility, this book engages the work of Levinas, Badiou, Derrida, Nietzsche, Husserl, Janicaud, Sartre, Ricoeur, and Marx. The time has come to move beyond the excesses of postmodernity and this book shows us how to do so.